Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

How far the ecowarrior will go: An ecofeminist reading of disney's Moana - Hernawati, Mala (3L: Language, Linguistics, Literature, 2021)
This article attempts to look into the fictional narrativization of women's significant and distinctive relationship with nature in Disney's Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney's princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney's animated princess films continuously adjust with the dynamics of global feminist discourse. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capitalisme; environnement; film d'animation; féminisme pop; histoire et politique; patriarcat; princesse disney; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; écoféminisme

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

La charge mentale écologique : un poids supplémentaire pour les femmes - Mathieu, Salomé (Milk Magazine, 2021)
Après la charge mentale domestique, la charge mentale écologique semble elle aussi aliéner tout particulièrement les femmes. Zoom sur ce concept inhérent aux combats écolo d’aujourd’hui, ce qu’il recoupe, et comment, peut-être, réussir à s’en affranchir.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; environnement; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; systèmes d'oppressions; thématiques; travail; travail invisible

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

YIWA Femmes autochtones et environnement - Takpanie Kiguktak, Olepika (2021)
Le premier panel de YIWA (Young Indigenous Women Action) sera animé par la fondatrice, Olepika Takpanie Kiguktak, et donnera la parole à quatre femmes autochtones impliquées à travers le Québec : Olivia Lya Thomassie, Uapukun Mestokosho, Maïtée Labrecque Saganash et Laura Fontaine. Elles aborderont des sujets qui sont importants pour elles comme leurs territoires, leurs identités, leurs luttes quotidiennes, leurs parcours inspirants et leurs motivations.
Directors: _:n22344 Producers: _:n22342
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; discours dominant; environnement; fem3600; femmes* autochtones; premier cycle; périodes historiques; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Après la charge mentale, la charge écologique ? Au vert avec la dessinatrice Emma - Vert (2021)
Grâce à ses bédés pédagogiques et engagées, elle a popularisé le concept de "charge mentale" avant de s'attaquer à un tas d'autres sujets compliqués, dont le climat. Avec la dessinatrice féministe Emma, nous avons discuté d'écologie au sein du foyer, de l'égalité femmes-hommes à l'épreuve de l'"effondrisme" et des petits gestes contre la fin du monde.
Keywords: 2000 à aujourd'hui; 2020-2029; anticapitalisme; approches et analyses; charge environnementale; charge mentale; charge émotionnelle; environnement; europe; france; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences